Pengaruh Partisipasi Anggaran dan Komitmen Organisasi terhadap Senjangan Anggaran - Nuke, Amanda Putri (COMPETITIVE, 2023)
This research was conducted on a case study of sectors in the district to examine whether budget participation, and organizational commitment affect budgetary slack. The population in this study were employees related to the budget who worked in the SKPD of the Sukabumi Regency Government. This study uses multiple linear regression analysis. The results of the study show that the first hypothesis shows that budgetary participation has an effect on budgetary slack and organizational commitment has an effect but is not significant on budgetary slack.